Neural Responses to Visual Food Cues: Insights from Functional Magnetic Resonance Imaging - García-García, I.; Narberhaus, A.; Marqués-Iturria, I.; Garolera, M.; Rădoi, A.; Segura, B.; Pueyo, R.; Ariza, M.; Jurado, M. A. (European eating disorders review, 2013)
The aim of this paper is to describe the patterns of functional magnetic resonance imaging activation produced by visual food stimuli in healthy participants, as well as in those with anorexia nervosa, bulimia nervosa, binge eating disorder and obesity. We conducted a systematic review of studies published in the last decade on normal and abnormal eating. This review suggested the existence of neural differences in response to the sight of food between healthy individuals, those with an eating disorder and obese subjects. Differences were identified in two brain circuits: (i) limbic and paralimbic areas associated with salience and reward processes and (ii) prefrontal areas supporting cognitive control processes. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.